Segregation process by gender : the case of the electronic data processing occupations - Tijdens, Kea [Verfasser]; Beckmann, Petra [Herausgeber] (My University, 1996)
This paper focuses on segregation processes by gender within one occupational category, i.e. the electronic data processing (EDP) occupations. These have not been male-dominated occupations from the beginning. In the fourties, the job of programmer, being the origin of all EDP occupations, was a female dominated occupation. It turned into a male-dominated one in the fifties. Women returned to these occupations during the eighties. However, they have not reached managerial levels. Four theories on sex segregation processes in these occupations are explored for their explanatory potential. The conclusions are drawn from a survey of the process of professionalisation in the EDP field over six decades, from a survey of the diversification in the EDP occupations and the proportion of women in these occupations. Employer's hiring practices are studied in great detail by analysing personnel changes over time in one firm's EDP department. (author's abstract)
Keywords: T 1.2 Historische Berufsbildungsforschung; S 6.4.9 IT-Berufe; G 2.4.5 Gender Mainstreaming; S 6 Berufsbereiche; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; G 1.2 Arbeitsmarkt; T 2 Theoretische Ansätze; S 5.3 Personalentwicklung; I 2.2.1 Westeuropa; Segregation; IT-Beruf; Historische Entwicklung; Geschlechterverteilung; Professionalisierung; Berufsdifferenzierung; Arbeitsmarkttheorie; Männerberuf; Frauenberuf; Personaleinstellung; Berufswahl; Quantitative Angaben; Niederlande; 1945-1990